Bloco das Flores: a trajetória de um bloco carnavalesco misto no carnaval de rua da cidade do Recife (1920-1930). - Mélo, Andréa Cadena Bandeira de (2023)
The study intends to analyze the trajectory and to contribute to the historiography of the Bloco das Flores, one of the first mixed carnival blocks that appeared in the city of Recife, Pernambuco, in the beginning of the 20th century during a period in which the city was undergoing transformations and modernization in the area of European customs. The carnival celebration, taking place in the context of these transformations that occurred in the city, provided the participation of women from the urban middle class - family girls - the opportunity to take to the streets to participate in carnival. Their presence gave the festivities a familiar character. In addition to introducing new elements to the parades such as the stick and rope band and female choir, their presence also contributed to the emergence of other blocks with a mixed typology in this period. The present research begins in the year 1920, the year indicated as the founding year of Bloco das Flores by documental records published by researchers about the Bloco das Flores and which served as a reference for this study. The time frame of this work concludes in 1937, the year in which the two important founders of the block--Pedro Salgado and Raul Moraes--died. As a basis for the studied subject, bibliographical collections of historians and researchers on the subject, articles produced on the subject and particularly collections of the local press of the time were examined as primary sources for a better understanding of the context of the party. The format chosen for writing the product was the publicity book.